Hepatitis C genotype and associated risks factors of patients at University Kebangsaan Malaysia Medical Centre - Mohamed, NA; Rashid, ZZ; Wong, KK; Abdullah, SA; Rahman, MM (Professional Medical Publications, 2024)
Indexed by WOS/Scopus